Trinidad and Tobago. Annual report 2005 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
Presents the results of IICA's management according to the aspects mentioned in the National Agenda, in relation to environmental management, promotion of food safety, international modernization, development of human capital, strengthening of rural communities, competitiveness, global trade and technical assistance